Hydroxytyrosol Inhibits MDSCs and Promotes M1 Macrophages in Mice With Orthotopic Pancreatic Tumor - Wang, Botao; Yang, Lei; Liu, Tianyu; Xun, Jing; Zhuo, Yuzhen; Zhang, Lanqiu; Zhang, Qi; Wang, Ximo (Frontiers in Pharmacology, 2021)
The poor immunotherapy of pancreatic cancer is mainly due to its complex immunosuppressive microenvironment. The Mediterranean diet contributes to low cancer incidence. Hydroxytyrosol (HT) derived from olive oil has multiple health-promoting effects, but its therapeutic effect on pancreatic cancer remains controversial. Here, we evaluated the inhibitory effect of HT on mouse pancreatic cancer, and the effect of HT on the immune microenvironment. We found that HT can inhibit the proliferation of Panc 02 cells through signal transducer and activator of transcription (STAT) 3/Cyclin D1 signaling pathway. In the tumor-bearing mice treated with HT, the orthotopic pancreatic tumors were suppressed, accompanied by a decrease in the proportion of myeloid-derived suppressor cells (MDSCs) and an increase in the proportion of M1 macrophages. In addition, we found that HT inhibited the expression of immunosuppressive molecules in bone marrow (BM)-derived MDSCs, as well as down-regulated CCAAT/enhancer-binding protein beta (C/EBPβ) and phosphorylation of STAT3. Moreover, HT enhanced the anti-tumor effect of anti-CD47 antibody in vivo. HT combined with plumbagin (PLB) induced more Panc 02 cells death than HT or PLB alone. This combination therapy not only inhibited the accumulation of MDSCs, but also promoted the infiltration of CD4+ and CD8+ T cells in the tumors. In summary, HT is a potential immunomodulatory drug for the treatment of pancreatic cancer.